Steering the Ship: Principles of Student Success for Organizational Change (Journal of School Administration Research and Development, 2021)
Researchers often use focus groups to collect data for qualitative research, but focus groups can also be used by organizational leaders to articulate participants’ values or principles - principles that can be used to guide organizational change. This paper examines one staff’s mobilization of a focus group to collect data for a research study they were conducting together to articulate programmatic principles. The collaborative nature of the group-work engaged and guided the participants in the generation of principles that were then used to guide program-wide development. Furthermore, the collaborative nature of the group encouraged engagement in the research from a partial participant and generated data that was used for triangulation in the grounded theory research be- ing conducted. The principles indeed guided the educators in their research and in changing their school and impacted both their self and collective efficacy.